2013
DOI: 10.1016/j.jare.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bacteria nesting the plant cover of north Sinai deserts, Egypt

Abstract: North Sinai deserts were surveyed for the predominant plant cover and for the culturable bacteria nesting their roots and shoots. Among 43 plant species reported, 13 are perennial (e.g. Fagonia spp., Pancratium spp.) and 30 annuals (e.g. Bromus spp., Erodium spp.). Eleven species possessed rhizo-sheath, e.g. Cyperus capitatus, Panicum turgidum and Trisetaria koelerioides. Microbiological analyses demonstrated: the great diversity and richness of associated culturable bacteria, in particular nitrogen-fixing bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Rhizosheaths act as an additional compartment in the rhizosphere of plants, being chemically and physically enriched and subsequently nourishing functional populations of microorganisms. Largely based on cultivation studies, rhizosheaths have been shown to harbour a range of different bacteria including members of the genera Bacillus , Paenibacillus , Enterobacter and Agrobacterium [ 11 ], [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rhizosheaths act as an additional compartment in the rhizosphere of plants, being chemically and physically enriched and subsequently nourishing functional populations of microorganisms. Largely based on cultivation studies, rhizosheaths have been shown to harbour a range of different bacteria including members of the genera Bacillus , Paenibacillus , Enterobacter and Agrobacterium [ 11 ], [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…G. diazotrophicus has been mainly found colonizing plants such as Pennisetum purpureum Schum (Reis et al, 1994;Baldani et al, 1997), Ipomea batatas Lamb (Paula et al, 1991), Coffea arabica L (Jimenez-Salgado et al, 1997), Ananas comosus L. (Tapia-HernĂĄndez et al, 2000), Polycarpon succulentum L., Fagonia arabica L., and Malva parviflora L. (Madhaiyan et al, 2004). Recently, the existence of G. diazotrophicus was reported in the rhizo-and-phyllo spheres of a number of desert plants in Sinai environment (Hanna et al, 2012). This bacteria species is capable of oxidizing ethanol to acetic acid, tolerate high concentrations of glucose (Kesters et al, 2006;Nakano and Fukaya, 2008) and to convert N 2 to NH 3 through biological nitrogen fixation (Cavalcante and Dobereiner, 1988;Kim and Rees, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Eruca sativa (salad rocket) is a winter annual undomesticated wild flowering plant that grows in nature mostly around the Mediterranean basin (50). It belongs to the Brassicaceae family, which includes various natural plant hosts for both Bacillus and Serratia species (51).…”
mentioning
confidence: 99%